Concomitant metal organic frameworks of cobalt(II) and 3-(4-Pyridyl)benzoate: optimized synthetic conditions of solvatochromic and thermochromic systems - Mehlana, Gift; Bourne, Susan A.; Ramon, Gaëlle; Öhrström, Lars (2016)
Two coordination networks, {[Co(34pba)2]·DMF}n (1 and 2), where 34pba is 3-(4-pyridyl)benzoate, were prepared by solvothermal methods. 1 is a three-dimensional metal organic framework formed by linking [Co2(34pba)8] clusters in a bcu net. 2 consists of single [Co(34pba)4] units in a tetragonal plane net of sql topology. The thermal conditions leading to their selective synthesis were established: 120 °C for 1 and 75 °C for 2. Their structures were solved and their thermal behavior was investigated. Further experiments established the activation energy for the desorption of the DMF molecules entrapped in their framework: 76(6)–106(16) kJ mol–1 for 1 and 49(3)–58(3) kJ mol–1 for 2. For 1, sorption experiments were carried out to demonstrate the ability of the coordination network to absorb different solvents, and the framework solvatochromic response was also ascertained.